2017
DOI: 10.12911/22998993/76209
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Household Toxic Hazardous Waste Generation Based on Economic Status and Topographic Regions in Semarang City, Indonesia

Abstract: Hazardous and toxic waste are not only produced by industry, but also by households. But in fact, the household activities also produce Household Toxic and Hazardous Waste (HTHW). Considering the potential of the impact of HTHW to worsening environment quality, the effort of HTHW management must have been started well. One important aspect in the management strategy is to determine the characteristics and the HTHW generation. The method used to determine the characteristics HTHW refers to SNI 19-2454SNI 19- -2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
2
2
0
1
Order By: Relevance
“…Other hazardous materials observed in the houses were used electronics & light bulbs, expired drugs and batteries. Similar findings have been reported [28,30,31].…”
Section: Household Hazardous Materials Management Practicessupporting
confidence: 91%
See 1 more Smart Citation
“…Other hazardous materials observed in the houses were used electronics & light bulbs, expired drugs and batteries. Similar findings have been reported [28,30,31].…”
Section: Household Hazardous Materials Management Practicessupporting
confidence: 91%
“…Furthermore, Insecticide, pesticides, rat anti-flea, herbicides were observed. Killing agents such as pesticides, herbicides, and/or insecticides have been identified as Household hazardous waste [30,33,34]. The study also observed automotive product from majority of the houses.…”
Section: Household Hazardous Materials Management Practicesmentioning
confidence: 80%
“…In addition to the comparison of from 11 countries, there are few studies that reported on the contribution/percentage HHW in domestic waste, including: Hangzhou, China 0,05 [19] Based on Table 1 shows that the percentage HHW in Semarang is similar to research done by Tuthill et al in Massachusetts, USA with a percentage of 5.7% [3]. But the results of this study is lower to that of Ziaee et al in the city of Tehran that its HHW percentage reaches 10% of the domestic waste [14] [20].…”
Section: Comparisons With Other Countriessupporting
confidence: 70%
“…Hasil penelitian yang dilakukan oleh Fikri, dkk tahun 2018 terkait timbulan sampah B3 RT, menunjukkan bahwa persentase sampah B3 RT golongan infeksius mendominasi dibandingkan dengan karakteristik B3 lainnya (terutama : popok dan pembalut wanita sekali pakai). Timbulan sampah B3 RT golongan infeksius mencapai 79%, sedangkan golongan beracun 13%, mudah terbakar dan meledak 6% dan terakhir adalah golongan sampah B3 RT korosif dengan persentase 2% (Fikri et al, 2017(Fikri et al, , 2018. Kuantitas tersebut hampir sama dengan yang ditujukkan di Kanada dan Amerika, bahwa rata-rata wanita membuang 1,3 juta ton pembalut setiap tahunnya (Priebe, 2010).…”
Section: Introductionunclassified